Automatic Initialization Of Contour For Level Set Algorithms Guided By Integration Of Multiple Views To Segment Abdominal CT Scans - Jawarneh, Mahmoud Saleh; Mandava, Rajeswari; Ramachandram, Dhanesh; Lutfi Shuaib, Ibrahim (2010)
This paper presents a new automatic initialization procedure for a level-set based segmentation algorithm that works on all slices for a given CT dataset.